The Effect of Healthy Breakfast Education with Islamic Comic Media on The Level of Knowledge of Elementary School Students - Hafizhatunnisa Hafizhatunnisa; Amilia Yuni Damayanti; Joyeti Darni (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2018)
The aims of this study was to look at the effect of healthy breakfast education with Islamic Comic Media on the level of knowledge of elementary school students. This study was a quasi-experimental type with pre-posttest control group design. The sampling was simple random method as many as 64 students, group A was given islamic comic media (n=32) and group B as control of the group (n=32). Nutrition knowledge level were obtained from filling out questionnaires. The influence of nutritional education media on increasing knowledge in both groups analyzed by Wilcoxon test, and continued with the Mann Whitney test. The results of the analysis showed that there was a significant increase in the level of knowledge in islamic comic group (p = 0,000). There is the influence of giving Islamic comic about healthy breakfast to elementary school-age students' knowledge.